2017
DOI: 10.3390/ijms18020382
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum (ER) Stress and Endocrine Disorders

Abstract: The endoplasmic reticulum (ER) is the organelle where secretory and membrane proteins are synthesized and folded. Unfolded proteins that are retained within the ER can cause ER stress. Eukaryotic cells have a defense system called the “unfolded protein response” (UPR), which protects cells from ER stress. Cells undergo apoptosis when ER stress exceeds the capacity of the UPR, which has been revealed to cause human diseases. Although neurodegenerative diseases are well-known ER stress-related diseases, it has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
64
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(68 citation statements)
references
References 198 publications
(211 reference statements)
1
64
0
3
Order By: Relevance
“…Changes in ATF6 expression and activity have been described in multiple human disorders, including the eye disease achromatopsia, myocardial infarction, stroke, amyloidosis, and a number of cancers (Ariyasu et al, 2017; Chiang et al, 2012; Manie et al, 2014; Plate et al, 2016; Urra et al, 2016; Zhou and Tabas, 2013). The finding that atf6 —/— mice have a higher incidence of neuronal cell death upon brain ischemia compared with wild-type mice argues for a protective effect of ATF6 (Yoshikawa et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in ATF6 expression and activity have been described in multiple human disorders, including the eye disease achromatopsia, myocardial infarction, stroke, amyloidosis, and a number of cancers (Ariyasu et al, 2017; Chiang et al, 2012; Manie et al, 2014; Plate et al, 2016; Urra et al, 2016; Zhou and Tabas, 2013). The finding that atf6 —/— mice have a higher incidence of neuronal cell death upon brain ischemia compared with wild-type mice argues for a protective effect of ATF6 (Yoshikawa et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…During physiological conditions, such as stem cell differentiation and proliferation, a certain level of ER stress may be required to compensate for increased cellular demands (Matsuzaki et al, ). However, pathophysiological conditions, such as obesity and diabetes, may induce ER stress as well (Ariyasu, Yoshida, & Hasegawa, ; Januszyk et al, ; Pagliassotti, Kim, Estrada, Stewart, & Gentile, ) and studies in mouse models have shown that both of these metabolic conditions may negatively affect stem cell behavior (Januszyk et al, ; D. Wu, Ren, Pae, Han, & Meydani, ). The mechanisms through which obesity, in the absence of comorbidity, affects stem cell functions, and BM‐MSCs in particular, are currently not fully understood, despite the presence of accumulating evidence indicating the importance of ER stress in the dysfunction of stem cells in obesity (Pagliassotti et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…PKR-like endoplasmic reticulum kinase (PERK), activating transcription factor 6 (ATF6), and inositol requirement 1 (IRE1), are well-characterized ER membrane-located proteins which sense ER stress. In the presence of ER stress, PERK is activated by trans-autophosphorylation, ATF6 activates expression of the ER chaperone immunoglobulin heavy-chain binding protein (BiP), and IRE1 activates splicing of X-box binding protein 1 ( Xbp1 ) mRNA via the PERK, ATF6, and IRE1 pathways, respectively (Ariyasu et al, 2017; Yoshida, 2007). PERK phosphorylation can be detected by immunoblotting, as phosphorylated PERK is associated with a mobility shift during SDS-PAGE (Harding et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…These data suggest that Δ3 GH can activate the three major ER stress pathways in vivo; however, activation of these ER stress pathways is not sufficiently strong to cause somatotroph apoptosis, since no apoptotic cells were detected by TUNEL assay, as described above (Fig 3B), and no caspase-3 activation was detected in Gh wtGH1/Δ3GH1 pituitary glands by immunoblotting (Fig 4A). In other established ER stress-related endocrine diseases, apoptosis is required to cause organ dysfunction (Ariyasu et al, 2017; Fonseca et al, 2010; Hayashi et al, 2009; Oyadomari et al, 2002; Yoshida, 2007). These data suggest that Δ3 GH-mediated ER stress is not likely to be causally related to the growth retardation in Gh wtGH1/Δ3GH1 mice.…”
Section: Resultsmentioning
confidence: 99%